Heavily nitrogen-doped acetylene black as a high-performance catalyst for oxygen reduction reaction. (June 2017) - Si, Yujun; Park, Moon Gyu; Cano, Zachary Paul; Xiong, Zhongping; Chen, Zhongwei
Abstract: Developing a non-precious metal catalyst for the oxygen reduction reaction (ORR) is a key to the commercialization of low-cost fuel cells. In this work, we prepare a heavily nitrogen-doped acetylene black (OAB-N) as an ORR catalyst by heat treating oxidized acetylene black in ammonia atmosphere. By pre-oxidizing acetylene black, nitrogen atoms can be effectively doped into its graphene structure. The content of nitrogen is as high as 6.37 at % in the OAB-N catalyst prepared from the pre-oxidized acetylene black. The results show that the pre-oxidization can improve the reactivity between acetylene black and ammonia, facilitating the doping of nitrogen atoms to acetylene black to form CN structures, especially pyridinic and pyrrolic CN structures with higher ORR activity. Encouragingly, the resulting OAB-N exhibits good catalytic activity to ORR with an onset potential of 1.0 V (vs. RHE) in 0.1 M KOH solution, high selectivity with an electron transfer number of 3.92 and an increased limiting current density in the cathodic process. Graphical abstract: